GenAI Chips in Cloud Data Centers: Driving Efficiency at Scale - Deepika Bhatia (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating Generative AI (GenAI) chips in cloud data centers marks a transformative advancement in managing artificial intelligence workloads and computational efficiency. This comprehensive article explores the revolutionary impact of these specialized processors on cloud infrastructure, focusing on three key areas: advanced cooling technologies, power management innovations, and applications in cloud computing. It examines how liquid cooling systems and immersion cooling technologies are revolutionizing thermal management in data centers while Dynamic Voltage Scaling (DVS) systems are optimizing power consumption. The article also investigates the significant improvements in AI training, inference capabilities, predictive analytics, and customer experience personalization enabled by these specialized chips. Furthermore, it delves into future implications, including the convergence with quantum computing and the development of more specialized processing units. This article demonstrates how GenAI chips fundamentally reshape cloud computing infrastructure while addressing crucial challenges in energy consumption and environmental sustainability.